(untitled) (Global Journal of Science Frontier Research, 2014)
The practice of continuous extraction of only the main boles from felled trees to meet high demand for timber is one major cause of deforestation in Ghana, but merchantable residues (branchwood and stem off-cuts) left un-extracted can be utilized to increase efficient wood utilization to conserve the forests and the entire ecological system. This study assessed harvesting efficiency, and quantified residues left in the forests after harvesting, to ascertain the extent to which residues utilization can affect forest preservation. Volumes of timber sections of 154 trees from 3 forest ecological sites were quantified using Smalian’s equation, after which harvesting efficiencies were determined. Results indicated merchantable residue quantity of 742.57m3 (24.69%) ranging from 16.34% for C. pentandra to (40.45%) for Khaya ivorensis and overall harvesting efficiency of 75.31% (ranging from 59.54%- mahogany to 83.66% -Ceiba pentandra). ANOVA indicated significant difference (P=0.000) at 95% confidence interval in harvesting efficiencies among species but not sites (P=0.435), and in both branchwoods and off-cuts volumes among species and sites (P=0.000). Strong positive correlation existed between extracted log volume and total merchantable wood (R2=0.866) than extracted log volume and total merchantable residue volume (R2=0.128). Extraction and utilization of merchantable residues were found to have the potential of conserving about 8 hectares of forest land. It was concluded that, extraction and eventual commercialization of merchantable residues can substantially improve efficiency in wood utilization and could conserve the forest vegetation and ecology.